A technique to assess perineuronal mediators. (2nd November 2018) - Goebel, Andreas; Lee, Maggie Kitman; Cacciola, Francesco; Cross, Andy; Eldridge, Paul
Abstract: Perineural activity of a variety of inflammatory and immune system mediators can activate peripheral nerves leading to the perception of pain. One example of such effects includes the activity of interleukin 1 beta (IL-1β); this inflammatory mediator, upon binding to IL-1R1 neuronal membrane receptors will rapidly induce protein kinases in damage-sensing neurons, consequently altering heat-activated ionic inward currents leading to increased neuronal sensitivity to harmful heat. The ability to detect such mediators in proximity to sensory nerves is therefore crucial to investigating the contributing roles of inflammation in human chronic pain. To date there is no recognized method to assess mediator profiles around human sensory nerve roots in vivo . A novel method is described that can assess these mediators in the human trigeminal system where the nerve leaves the brain stem in its pre-ganglionic portion. Mediator levels are shown to change between sample locations on the trigeminal nerve root in patients with trigeminal neuralgia. This methodology may therefore be used to shed insights as to the pathophysiology of trigeminal neuralgia, which may in turn influence clinical decisions concerning the natural history, and treatment options.